Pesantren and World Peace: Considering the Functional Role of Pesantren in Creating Moderate Santri Pioneers of Peace - Kurniawan, Syamsul; Taufik, Egi Tanadi; Fitriyani, Feny Nida (Nadwa: Jurnal Pendidikan Islam, 2024)
The focus of this article is pesantren and world peace, which discusses the functional role of pesantren in creating moderate santri. This article is reflective, and the result of a literature study carried out by the authors. Based on the results of the author's study, the future of peace for the nation and the world depends on our perspective and abilities, including santri as part of the world community, especially in building mutual commitments in the context of religion, nation, and part of the world community that is moderate in its religious diversity. Based on data from the Indonesian Ministry of Religion, there will be at least 39,043 pesantren in 2022/2023, with a total number of santri of 4.08 million, which certainly has great potential. However, to make pesantren a basis for religious moderation, their durability can be tested, especially in the context of their functional role in world peace. Pesantren’s resilience can be tested from the achievement of its functional prerequisites, both in terms of adaptation, goal attainment, integration, and latency, which should be in line with the needs of creating moderate santri who pioneer peace. However, it is not impossible to become dysfunctional, if it is on the contrary when pesantren is closer to religious radicalism. In addition, one of the biggest challenges is how pesantren can produce moderate santri in this fast-paced digital era, where the influence of cyberspace is often more dominant than conventional learning.